2007
DOI: 10.1152/ajpcell.00095.2007
|View full text |Cite
|
Sign up to set email alerts
|

Vaticanol B, a resveratrol tetramer, regulates endoplasmic reticulum stress and inflammation

Abstract: Enhanced endoplasmic reticulum (ER) stress has been implicated in various pathological situations including inflammation. During a search for compounds that regulate ER stress, we identified vaticanol B, a tetramer of resveratrol, as an agent that protects against ER stress-induced cell death. Vaticanol B suppressed the induction of unfolded protein response-targeted genes such as glucose-regulated protein 78 (GRP78) and C/EBP-homologous protein (CHOP) after cells were treated with ER stressors. Analysis in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
57
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 29 publications
(39 reference statements)
5
57
0
Order By: Relevance
“…1A, ER stress induced the upregulation of IL-1b and TNF-a gene expression in a manner similar to LPS, indicating that an ER stress-induced downstream event can regulate the expression of proinflammatory cytokines. Consistent with previous reports (19), the expression of CHOP, a classic ER stress response, was induced by TM treatment, but not by LPS treatment (Supplemental Fig. 1A).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1A, ER stress induced the upregulation of IL-1b and TNF-a gene expression in a manner similar to LPS, indicating that an ER stress-induced downstream event can regulate the expression of proinflammatory cytokines. Consistent with previous reports (19), the expression of CHOP, a classic ER stress response, was induced by TM treatment, but not by LPS treatment (Supplemental Fig. 1A).…”
Section: Resultssupporting
confidence: 92%
“…ER stress-induced GSK-3b activation differently regulates IL-1b and TNF-a mRNA expression in cultured macrophages ER stress-mediated UPRs have been suggested to be involved in the activation of NF-kB, which regulates genes encoding proinflammatory cytokines such as IL-1b, TNF-a, and IL-6 (18)(19)(20)(21)(22). Moreover, activation of NF-kB and expression of the proinflammatory cytokines have been observed in the liver of mice challenged with the pharmacologic ER stress inducer TM (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies showed that, in addition to 4-PBA, treatment with small molecule chaperones can restore proper protein folding and ER function. These chaperones include taurine-conjugated ursodeoxycholic acid, vaticanol B, and others, which were shown to decrease aggregate formation and prevent an ER stress response (48,49). Although these treatments have shown promising results, they will likely have to be simultaneously evaluated for offtarget effects on the many other cellular pathways that link ER stress and cellular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kaser et al 7) reported that the transcription factor X-box binding protein 1 (XBP1), which is an important key to ER stress response, is involved in the genetic risk of onset of IBD in humans. These findings suggest a possible correlation between IBD and ER stress.We reported that dantrolene, an antagonist of ryanodine receptors in the ER, and some antioxidants such as a-tocopherol, partly prevented tunicamycin-induced cell death in F9 homocystein-induced ER protein null cells.8) Using this cell line, our group and others have reported that 103 plantderived compounds 9,10) and 200 synthetic compounds including dibenzoylmethane (DBM) derivatives, 11) carbazole derivatives, 12) and pyrimidine derivatives were screened previously, and some DBM derivatives improved cell viability after tunicamycin treatment at a level similar to that achieved by dantrolene in F9 Herp null cells.11) However, it remains unclear whether DBM derivatives that have protective effects against ER stress are effective against colitis.Nuclear factor kB (NF-kB) is a dimeric transcription factor that induces the expression of genes involved in the inflammatory process. Activation of NF-kB has been observed in the mucosa of patients with ulcerative colitis, 13) and butyrate has been shown to inhibit NF-kB activation in lamina propia macrophages of patients with ulcerative colitis.…”
mentioning
confidence: 93%